2019
DOI: 10.1038/s41598-018-37108-2
|View full text |Cite
|
Sign up to set email alerts
|

A new application of Trichoderma asperellum as an anopheline larvicide for eco friendly management in medical science

Abstract: Microfungal applications are increasing daily in the medical science. Several species of Trichoderma are widely used in agricultural fields as biological control and plant growth promoting agents. The application of Trichoderma asperellum as an entomopathogenic fungus against the Anopheles mosquito, a vector of malaria, is a novel control approach. Controlling malaria with eco-friendly management practices is an urgent need. We isolated three T. asperellum from different natural sources using serial dilution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Podder and Ghosh [56] showed that Trichoderma asperellum could be used against Anopheles mosquitoes, vectors of malaria. They investigated the efficacy of crude methanolic extracts and different methanolic fractions of the fungal extracts against anopheline larvae and concluded that the crude methanolic extract has new applications for the control of Anopheles spp.…”
Section: Effect Of Ingestion or Contact With S And Effects Of Volatilmentioning
confidence: 99%
“…Podder and Ghosh [56] showed that Trichoderma asperellum could be used against Anopheles mosquitoes, vectors of malaria. They investigated the efficacy of crude methanolic extracts and different methanolic fractions of the fungal extracts against anopheline larvae and concluded that the crude methanolic extract has new applications for the control of Anopheles spp.…”
Section: Effect Of Ingestion or Contact With S And Effects Of Volatilmentioning
confidence: 99%
“…are saprophyte fungi whose natural habitats are the soils, where they perform many functions relevant to plant health. These fungi secrete auxins that promote root growth and defence mechanisms against different pathogens, insects and nematodes (Zhang et al 2015; Podder and Ghosh 2019). Tr ichoderma sp.…”
Section: Introductionmentioning
confidence: 99%
“…Larval PO is associated with melanin biosynthesis and haemocyte production for self defense; decreased PO indicates reduction of immunity which provide favourable conditions for pathogens growth inside the insect's body 25 . In our previous study, we have reported decreased larval phenol oxidase content in ME treated larval hemolymph and cuticle, in comparison with control 11 . For mycochemistry of ME , the crude ME was fractionized, and each fraction was evaluated against anopheline larvae.…”
Section: Discussionmentioning
confidence: 74%